2016
DOI: 10.1111/andr.12240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA methylation at imprinted DMRs in the spermatozoa of oligozoospermic men in association withMTHFRC677T genotype

Abstract: SUMMARYAltered DNA methylation has been previously identified in the spermatozoa of infertile men; however, the origins of these errors are poorly understood. DNA methylation is an epigenetic modification which is thought to play a fundamental role in male germline development. DNA methylation reactions rely on the cellular availability of methyl donors, which are primarily products of folate metabolism, where a key enzyme is methylenetetrahydrofolate reductase (MTHFR). The MTHFR C677T single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…Those reports suggested a MTHFR polymorphism independent mechanism in aging and cell-type specific global DNA methylation. Furthermore, a similar results were reported in a study of individuals with or without oligozoospermic which showed no significant association between DNA methylation in spermatozoa and the MTHFR C677T genotypes although a trend for higher incidence of methylation alterations in severe oligozoospermic infertile men with CT genotypes were observed 34 , suggesting that a much more complicated or indirect interactions between MTHFR polymorphism and methylation are involved.…”
Section: Mthfr Polymorphismsupporting
confidence: 84%
“…Those reports suggested a MTHFR polymorphism independent mechanism in aging and cell-type specific global DNA methylation. Furthermore, a similar results were reported in a study of individuals with or without oligozoospermic which showed no significant association between DNA methylation in spermatozoa and the MTHFR C677T genotypes although a trend for higher incidence of methylation alterations in severe oligozoospermic infertile men with CT genotypes were observed 34 , suggesting that a much more complicated or indirect interactions between MTHFR polymorphism and methylation are involved.…”
Section: Mthfr Polymorphismsupporting
confidence: 84%
“…Contrariwise, no correlation was found between methylation errors at H19 and MEST genes and inactivating MTHFR C677T single-nucleotide polymorphism (SNP) [a cytosine (C) to a thymine (T) substitution at position 677] in sperm DNA from infertile patients with defective semen parameters. However, a higher incidence trend of aberrant DNA methylation among severe oligozoospermic infertile males carrying C677T genotype was observed (Louie et al, 2016).…”
Section: Gene Methylation Changesmentioning
confidence: 88%
“…Methylated regions of imprinted genes are established during spermatogenesis and maintained in mature spermatozoa by DNMT1 (Tang et al, ). Recently, a study demonstrated that abnormal DNA methylation‐mediated genomic imprinting is associated with oligozoospermia in men (Louie et al, ). In addition, DNA methylation levels in human spermatozoa from patients with unexplained infertility had different methylation patterns when compared to those of fertile men (Urdinguio et al, ).…”
Section: Discussionmentioning
confidence: 99%